Implementation Design of Corporate Farming using Warehouse Receipt System Approach in Central Java. Issue 1 (September 2020) - Budiraharjo, Kustopo; Sunarno,; Solikhin,; Kunaedi, Agung; Darwanto,
Abstract: Corporate farming is farmland merger activity jointly organized by farmers in an integrated single management. This system can be a solution for many of the problems faced by farmers today. Business efficiency, quality standardization, and effectiveness and efficiency in managing the utilization of resources are expected when the company's agricultural system is implemented. Paddy farming in Central Java is still dominated by narrow-scale farming activities that are managed individually. This results in diverse productivity and is economically less efficient, resulting in low competitiveness. Farming activities currently carried out by farmers will be more efficient if managed by implementing a corporate farming system and supported by the Warehouse Receipt Integrated System makes microfinance institutions interested in distributing funds to capital farmers. The warehouse receipt system is supported by the concept of comparative agriculture, it is hoped that the synergy of both can increase the capital and income of farmers in Central Java.